Konversi Lahan Sawah di Kota Bogor dan Strategi Anggaran dalam Mengendalikannya - Oni Hidayati; Hermanto Siregar; A. Faroby Falatehan (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2017)
Conversion of agricultural land in urban areas is most prevalent in wetlands, thus threatening food availability and loss of multifunctional land. In the last five years, the wetland area in Bogor City has dropped dramatically to 321 ha (BPS of Bogor City, 2016). Control of the rate of conversion of wetland in Bogor City is regulated by Local Regulation number 8 year 2011 concerning Bogor City Spatial Plan (RTRW Kota Bogor) 2011-2031. However, its implementation is less effective so that there is a need for economic instruments to support it. The purpose of this study is to describe the wetland conversion in Bogor City and budgetary strategies in order to control it. Spatial analysis with overlay method was used to and resulted in a land conversion pattern which was dominated by housing area of 1 137.33 ha (47.08%) and garden 254.28 ha (10.53%). The conversion pattern was used as the basis of multiple linear regression analysis of factors affecting wetland area in Bogor City during 2000-2015 which results were: production amount (significant at α 1%); building area (significant at α 5 %); realization of Bogor City Agricultural Service budget (not significant) with R2 value = 86.6%. Wetland conversion control was conducted through budget strategies which are analyzed with Analitycal Hierrachy Process (AHP) calculation, resulting as follows: (1) socialization budget; (2) budget for formulating local regulation; (3)budget sharing with the central/provincial government; (4) streamlining the role of the private; (5) budget supervision; (6)budget for (land banking); (7) incentives and disincentives for farmers.